Mosque Ta'mir Policy on the Worship at the Mosques During the COVID-19 Pandemic: Maqasid Al-Shari'ah Perspective - Syafaq, Hammis; Musyafaah, Nur Lailatul; Candra, Marli; Hasyim, Muh. Fathoni (Sinergi International Journal of Islamic Studies, 2025)
During the COVID-19 pandemic, the government of the Sidoarjo district in Indonesia implemented regulations regarding worship in mosques, leading to both support and opposition among the community. This article examines the mosque management policies related to the mechanisms of prayer during the pandemic in Sidoarjo. The research adopts an empirical approach empowered by sociological jurisprudence, focusing on how law interacts with society. Data was collected through observations, interviews, and documentation and analyzed deductively using the maqasid al-shari'ah theory. The study reveals several key findings. First, nine mosques complied with Regent Regulation Number 31 of 2020, which mandated the suspension of religious activities within mosques. In contrast, two mosques did not follow this regulation. Second, all mosques adhered to Regent Regulation Number 32 of 2020, which permitted religious activities in places of worship, provided that health protocols were followed. Third, none of the mosques complied with Regent Regulation Number 44 of 2020, which stipulated that religious activities must be halted if anyone present tested positive for COVID-19. Based on these findings, mosque management that adhered to the Sidoarjo Regent's regulations in response to COVID-19 was fulfilling the principles of preserving religion and safeguarding life as outlined in maqasid al-shari'ah. Conversely, mosque management that did not comply with the regulations was acting contrary to these principles. The impact of the COVID-19 pandemic has thus indirectly influenced mosque management policies regarding worship practices. To align with maqasid al-shari'ah, mosque management should comply with the Sidoarjo Regent's regulations to promote benefits and avoid harm.